Energy-using appliances and energy-saving features: Determinants of ownership in Ireland - Joe O'Doherty; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
Energy usage and energy efficiency are of increasing concern in Ireland. Regression analyses on a large household micro-dataset reveal that those homes that have more energy-saving features are also likely to have a high 'potential energy use'. Statistically significant dwelling features include location, value and dwelling type, while household features such as income, age, period of residency, social status and tenure type are also important.
Keywords: 330; Energy use; Ireland; appliance ownership; energy efficiency; Energiekonsum; Energiesparen; Privater Haushalt; Irland